When Numbers Make Laws: A Study of the Effect of Social Movements on Legislative Action and Related Concerns - Yang, Inchan (Technium Social Sciences Journal, 2020)
With a recent surge in demonstrations and social movements, it is necessary to identify and acknowledge the potential problems that may arise from introducing legislation based on social movements. Case studies of legislation, ranging from minor to major reforms, demonstrate that even if a social movement achieves its immediate goals of changing the legislation, it may be ultimately unsuccessful. If the reformed law fails to bring about effective change to the society or entail hugely problematic side-effects, the social movement could not be considered as an entirely successful one. Following the analysis of a few case studies, this article explores psychological phenomena to address potential concerns over the irrationality of collective behaviour, with a consideration of the different nature of social movements between the US, an individualist culture, and South Korea, a collectivist culture. This article identifies the potentially problematic aspects of social movements and urges legislators to deliberate over changes to the law explicitly demanded by the public. It is not intended to condemn social movement itself- it simply wishes to demonstrate that social movements are not necessarily good legislators, and that careful consideration of social movements is essential to bring about truly effective changes to the society.